Fundamentals of muscle training of the horse: New paradigms for sports medicine specialists - José Luis López Rivero (Atti della Accademia Peloritana dei Pericolanti - Classe di Scienze Medico-Biologiche)
As the main purpose of training is to modulate the muscular physiology according to the functional demands of each sporting discipline, it seems reasonable that those who in practice direct the training of the horse should know the fundamentals of these adaptations. Thus, it is very important to be clear that today's horse has developed innately and through selective breeding over generations outstanding muscular qualities within the animal kingdom, which are difficult to improve in practice. Thanks to studies carried out over the last 3-4 decades we now have certainty about the muscular changes we can expect in response to certain types of training methods and how these adaptations improve athletic performance. Of practical interest are the muscle genomics studies conducted in the last decade, which allow us to examine candidate genes for targeted selection and early prediction of performance, and to objectively monitor the practical training of these super-athletes. With all this, the equine sports medicine veterinarian now has an arsenal of scientific knowledge and state-of-the-art techniques to compete for the practical training of equine athletes, which is no longer largely empirical, as is unfortunately still the case today